STRATEGI RESOLUSI KONFLIK LAHAN OLEH PT. SURYA BRATASENA PLANTATION DENGAN MASYARAKAT DI KECAMATAN PANGKALAN KURAS KABUPATEN PELALAWAN RIAU - Raja Malinda Jeliantika; Harapan Tua (Universitas Halu Oleo, 2021)
Conflicts in oil palm plantation companies cannot be separated from land problems with the community. This conflict occurred due to the existence of community land within the PT. Surya Bratasena Plantation due to an error in the previous shaving. The purpose of this research is to see and understand how the company strategy in its efforts to settle land with the community and to find out what factors are the obstacles to the implementation of the Land Conflict Resolution Strategy made by PT. Surya Bratasena Plantation. The theory used in this research is conflict resolution theory with three indicators, namely negotiation, mediation and arbitration. To answer this research problem, researchers used qualitative methods using data collection techniques such as interviews and documentation, then analyzed and looked for conclusions about these problems. The results of this study indicate that the strategy that has been made by PT. Surya Bratasena Plantation and offered to the community can solve the problem without involving a third party in its resolution. The inhibiting factor in carrying out this strategy is the presence of outsiders as provocateurs to make people not want to make peace.